Decentralisation Hybridized - Annina Aeberli (Graduate Institute Publications, 2012)
South Sudan is undergoing a process of internationally-supported state building of which decentralisation forms part. For the people, decentralisation is understood as a right to self-rule based on native-stranger dichotomies and as a means of appropriating and incorporating an abstract and distant state into the local context. The South Sudanese government, in contrast, sees decentralisation primarily as a tool for service delivery and development. Conversely, the international community, in...